2017
DOI: 10.22495/cbv13i1c1art3
|View full text |Cite
|
Sign up to set email alerts
|

Board meeting frequency and corporate social responsibility (CSR) reporting: Evidence from Malaysia

Abstract: This study aims at determining the effectiveness of board meeting frequency on Corporate Social Responsibility (CSR) reporting by public listed companies on the Main Market of Bursa Malaysia. A CSR reporting index consisting of 51 items was developed based on six themes: General, Community, Environment, Human Resource, Marketplace and Other. A content analysis was used to determine the extent of CSR reporting. An Ordinary Least Square (OLS) regression was employed in determining the association between board m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 58 publications
1
15
1
6
Order By: Relevance
“…This corroborates the findings of Dye (2001), Verrecchia (2001), Fernandes (2012), where the positive information is strategically disclosed and highlighted, while the negative is less so, or omitted, resulting in an absence of information, or the minimization of the disclosure of environmental liabilities. In addition, from the perspective of socio-environmental strategy, it was found that the low disclosure of negative information was specifically made merely to comply with government regulations, as proposed by Alperstedt et al (2013). Table 3 presents the results obtained in the total of the presence of terms relative to the CSI and socio-environmental aspects, between the years 2008 to 2013 in the companies.…”
Section: Description and Analysis Of The Resultsmentioning
confidence: 99%
“…This corroborates the findings of Dye (2001), Verrecchia (2001), Fernandes (2012), where the positive information is strategically disclosed and highlighted, while the negative is less so, or omitted, resulting in an absence of information, or the minimization of the disclosure of environmental liabilities. In addition, from the perspective of socio-environmental strategy, it was found that the low disclosure of negative information was specifically made merely to comply with government regulations, as proposed by Alperstedt et al (2013). Table 3 presents the results obtained in the total of the presence of terms relative to the CSI and socio-environmental aspects, between the years 2008 to 2013 in the companies.…”
Section: Description and Analysis Of The Resultsmentioning
confidence: 99%
“…The average frequency of meetings in the banking industry is 5 times with a range of 4 to 6 times by each bank. Because, the frequency of board meetings can be interpreted as the delivery of information on monitoring activities that have been carried out (Ju et al, 2017). Board meetings are an opportunity for members to share meaningful knowledge and exchange ideas between themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of board meetings can be interpreted as the delivery of information on monitoring activities that have been carried out (Ju et al, 2017). Board meetings are followed basically to conduct evaluations and provide input to directors to share information and exchange meaningful ideas for future company development.…”
Section: Theoritical Reviewmentioning
confidence: 99%
“…33 / PJOK.04 / 2014 article 16, the board of directors is required to hold board of directors meeting regularly at least once a month. Board of directors meeting is an appropriate way to effectively communicate their various responsibilities in achieving sustainable company goals (Ju Ahmad et al, 2017;Vafeas, 1999). However, board of directors meetings cannot always increase the effectiveness and disclosure of CSR.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Several previous studies have discussed the relationship between board meeting with CSR disclosures, but they still cause debate. Ju Ahmad et al (2017) explain that board meetings have a positive influence on CSR. Giannarakis (2015) also explained that board meeting had a positive effect on corporate social responsibility disclosure (CSRD).…”
Section: Introductionmentioning
confidence: 99%